Origin of Brahmi Script from Logographic Elements: An Analysis - Paras Duhan (Integrated Journal for Research in Arts and Humanities, 2022)
When it comes to language and literature, the richness of a culture can only be comprehended via reading and listening. Brahmi is believed to have been responsible for the script of all northern Indian languages except for Urdu. The result of a lengthy and tedious process. There are currently over 200 different languages and dialects spoken throughout India. Some are extensively employed, while others are only found in a single location of the country or planet. Only twenty-two of these amendments has made it into the text of our country's founding constitution. In addition to Braj Bhasha, Avadhi who is spoken in the Oudh region, Bhojpuri, Magadhi, and Maithili which is spoken in Mithila, Rajasthani who is spoken in Rajasthan, and Khadi Boli which is spoken around Delhi. A substantial number of people speak Hindi in its various forms. Another script, known as Brahmi, was also established in the region during this period and was used throughout India and the rest of South Asia at the same time. Even though historians, archaeologists, and epigraphists have been interested in Brahmi Script for centuries, the script's varied forms, structures, and typographical peculiarities as an alphabet have been mostly overlooked and never examined. Within the scope of this paper, we shall look at the origins of the Brahmi script as a type of logography. Historical appreciation for the distinct anatomical symmetry and phonetic logic of the Brahmi script exists. This has led some outsiders to think that it is an import, yet a consensus has developed over time. "Brahmi" is no longer thought to be a stolen script, but rather an Indigenous one that developed over time. Brahmi is a typographic entity that is basic yet graceful, bold yet lyric, distinct yet easy to recall, symmetrical with decent legibility even when scaled-down, and generally easy to recognise when touched on with closed eyes as a typographic entity. Brahmi is a typeface with a wide range of distinct features. This study investigates the history of the Brahmi script as a logographic element.